PERBEDAAN KEMATANGAN EMOSIONAL SISWA SMA DENGAN SANTRI PONDOK PESANTREN - Budi Johan; Emiliya Alkhansa; Shafira Fusta Ramadhani; Titi Latifah; Syadad Syadad; Alya Nur (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
This study aims to analyze the differences in emotional maturity between high school students (SMA) and students in Islamic boarding schools (santri). The main focus is to compare emotional maturity between these two groups in the context of different educational environments. Information sources were obtained through searches in various relevant sources, including national journals discussing the morals of students in Islamic boarding schools and outside boarding schools. The research method used was Literature Review with the aim of collecting, summarizing, and analyzing findings from previous research on emotional maturity of high school students and santri. Data collection was obtained by documenting relevant articles from similar studies. A total of 8 national journal articles were used in this study and were retrieved from the Google Scholar database.